Does financial literacy improve financial inclusion? Cross country evidence - Antonia Grohmann; Theres Klühs; Lukas Menkhoff (Deutsches Institut für Wirtschaftsforschung (DIW), 2017)
While financial inclusion is typically addressed by improving the financial infrastructure we show that financial literacy, representing the demand-side of financial markets, also has a beneficial effect. We study this effect at the cross-country level, which allows to consider institutional variation. Regarding "access to finance", financial infrastructure and financial literacy are mainly substitutes. However, regarding the "use of financial services", the effect of higher financial literacy strengthens the effect of more financial depth. The causal interpretation of these results is supported by IV-regressions. Moreover, the positive impact of financial literacy holds across income levels and several subgroups within countries.
Keywords: O1; G2; D14; 330; financial inclusion; financial literacy; financial institutions; financial development